PERAN PENDEKATAN MULTIKULTURAL DALAM PEMBELAJARAN BAHASA INDONESIA UNTUK MEMPERKUAT KEBERAGAMAN BUDAYA - Sariasih, Yanti; Jendriadi (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2025)
The multicultural approach in Indonesian language learning plays a strategic role in strengthening cultural diversity amid the challenges of globalization and digitalization. This article aims to analyze the relevance and implementation of a multicultural approach in the context of Indonesia's diverse education system, with a focus on Indonesian language learning as a unifying tool for the nation. The research method used is a literature review, examining various theoretical and empirical sources related to multicultural education. The results indicate that the multicultural approach not only teaches language skills but also instills values of tolerance, inclusivity, and appreciation for cultural diversity. Its implementation includes integrating regional literary works, using diverse media, and employing collaborative and interactive learning methods. This approach also encourages critical reflection on social injustices and strengthens national identity. The conclusion of this article emphasizes that the multicultural approach in Indonesian language learning is an effective solution for fostering a tolerant, creative generation ready to face global dynamics while preserving national unity within the framework of Bhinneka Tunggal Ika.